Use of digital educational resources in teaching physics - Gabdullina, G.L.; Gabdullina, A.T.; Medetbekova, A.A. (Recent Contributions to Physics, 2017)
The article discusses the role of digital educational resources in education and their impact on the development of society as a whole. The ways and opportunities of teaching physics based on digital resources. The importance of digital educational resources for quality education was shown. In the work it was proposed to use digital educational resources for learning section of General physics course “Electricity and magnetism” for KazNU students. Digital educational resources were developed with the help of a program Аdobe Flash Professional CS5.5. In the work considered the feasibility of monitoring and verification of learning through the test and test tasks of different formats. In the proposed digital resources the module «test» created using Аdobe flash professional CS5.5 and programmed in the language Аctionscript. It is shown that the digital learning resource can fully provide the knowledge, learning and consolidation of educational material and promote the training of qualified personnel in the field of natural Sciences.